An unusual case of osteoid osteoma occurring simultaneously with an ameloblastoma: a case report. (20th May 2016) - Martin, L.; Kennedy, G.; Thorne, L.; Ayliffe, P.; Speight, P.M.
Abstract: Dual pathology of head and neck lesions is well reported in patients with syndromes; however, only one previous case of an odontogenic tumour associated with a benign bone lesion can be found. Osteoid osteoma is a rare benign osteogenic tumour of unknown aetiology, commonly affecting the long bones of males, rarely occurring in the head and neck. This case report reviews an adolescent presenting with an ameloblastoma and an unsuspected additional bony lesion, subsequently diagnosed as osteoid osteoma. This report demonstrates not only unusual clinical presentation occurring within a non‐syndromic patient but also highlights the importance of vigilance in clinical and radiographic examination.